1989
DOI: 10.1007/bf00257141
|View full text |Cite
|
Sign up to set email alerts
|

Curvature-electric effects in artificial and natural membranes studied using patch-clamp techniques

Abstract: Methods for applying sound pressure to membrane patches formed at the tips of patch-clamp pipettes have been developed. Artificial membrane patches were formed from diphytanoyl phosphatidylcholine using a pipette dipping technique. Natural membrane patches were excised (inside-out mode) from collagenase-treated locust muscle membrane. Curvature-electric signals were registered under both voltage clamp and current clamp conditions. The phenomenon of flexoelectricity in membranes has previously been attributed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 8 publications
0
21
0
Order By: Relevance
“…However, in the presence of curvature, this symmetry argument does not apply, and one expects an electrical field generated by curved membranes. Petrov named this phenomenon "flexoelectricity" and demonstrated the effect in experiments similar to those by Ochs and Burton (15) but interpreted differently as curvature-induced polarization (43,44). In several further papers the authors applied the concept of flexoelectricity to biomembranes and proposed a coupling of flexoelectricity to ionic currents through channel proteins (45,46).…”
Section: Discussionmentioning
confidence: 83%
“…However, in the presence of curvature, this symmetry argument does not apply, and one expects an electrical field generated by curved membranes. Petrov named this phenomenon "flexoelectricity" and demonstrated the effect in experiments similar to those by Ochs and Burton (15) but interpreted differently as curvature-induced polarization (43,44). In several further papers the authors applied the concept of flexoelectricity to biomembranes and proposed a coupling of flexoelectricity to ionic currents through channel proteins (45,46).…”
Section: Discussionmentioning
confidence: 83%
“…The former is a lipid bilayer which can be considered a lipotropic phase LC 101. This similarity suggests that cellular membranes will also exhibit flexoelectric effects 12, 102–104. Indeed, research conducted on both artificial cell membranes as well as on natural cells has revealed both direct and converse flexoelectricity.…”
Section: Flexoelectricity In Soft Materialsmentioning
confidence: 99%
“…With the exception of graphene, boron nitride and (to some degree) graphene nitride [12][13][14], a characterization of the flexoelectricity in other 2D materials is still missing. In particular, we note that to date, flexoelectricity has not been experimentally evaluated for any of the 2D inorganic materials-however, as described in the main text, considerably more progress has been made in the case of lipid bilayers [57][58][59][60][61].…”
Section: What Are Some Open Areas Of Research In Flexoelectricity?mentioning
confidence: 99%